ANIMASI 2D CERITA RAKYAT PAK SALOI “BERBURU KIJANG” DENGAN MENERAPKAN METODE MDLC - Apriadi, Apriadi; Mitha, Mitha; Noferianto Sitompul; Salahuddin, Salahuddin (UNIVERSITAS STEKOM, 2023)
2D-based animated films are a medium that is liked by children to adults, through social media 2D animation can be disseminated so that anyone who sees it will get information.Helping to introduce tradition through 2D animation is the aim of this research, namely with the title “Graphic Design Of Objects In Making 2D Animation Films Of Pak Saloi Folklore “Hunting Deer” By Applying The MDLC Method using the Multimedia Development Life Cycle (MDLC) method which has 6 stages, namely, concept, design, material collecting, assembly, testing and distribution. It is hoped that the existence of this 2D-based animated film can become a medium of information about Mr.Saloi Folklore “Hunting the Deer”.